Visualizing with text - Brath, Richard (Boca Raton : CRC Press, 2020)
Visualizing with Text uncovers the rich palette of text elements usable in visualizations from simple labels through to documents. Using a multidisciplinary research effort spanning across fields including visualization, typography, and cartography, it builds a solid foundation for the design space of text in visualization. The book illustrates many new kinds of visualizations, including microtext lines, skim formatting, and typographic sets that solve some of the shortcomings of well-known visualization techniques. Key features: More than 240 illustrations to aid inspiration of new visualizations Eight new approaches to data visualization leveraging text Quick reference guide for visualization with text Builds a solid foundation extending current visualization theory Bridges between visualization, typography, text analytics, and natural language processing The author website, including teaching exercisesand interactive demos and code, can be found here. Designers, developers, and academics can use this book as a reference and inspiration for new approaches to visualization in any application that uses text.
Contents List of Figures and Credits, xvii Foreword, xxiii Preface, xxvii About the Author
59 3.2.10 Shifting Baseline and Text on a Path 61 3.3 NON-TYPE VISUAL ATTRIBUTES 62 3.3.1 Size 63 3.3.2 Rotation 64 3.3.3 Fill Color 64 3.3.4 Outline and Outline Color 64 3.3.5 Gradients or Drop-Shadows 65 3.3.6 Superimposition and Contrast 66 3.3.7 Distortion and Extrusion 66 3.3.8 3D Orientation 66 3.3.9 Motion 67 3.3.10 More: Texture, Blur, Transparency, Etc.
67 3.4 MARKS AND TEXT SCOPE 67 3.4.1 Point Marks: Characters, Codes, Syllables, and Words 68 3.4.2 Line Marks: Phrases and Sentences 69 3.4.3 Area Marks: Paragraphs and Chapters 69 3.4.4 Readability of Text 71 3.5 TEXT LAYOUTS: PROSE, TABLES
OCLC-licensed vendor bibliographic record.
Keywords: Information visualization; Graphic design (Typography); Charts, diagrams, etc; COMPUTERS / General; COMPUTERS / Computer Graphics / General; COMPUTERS / Computer Graphics / Game Programming & Design